POETIC VOICE OF ALMA LUZ VILLANUEVA’S “MOTHER, MAY I?” - Nilufar Furkatovna Botirova (Лучшие интеллектуальные исследования, 2023)
Annotation: This article discusses chicano poetry and the general themes of it. Also it explains Alma Luz Villanueva’s masterpiece: “Mother, may I?” in which the feminist poet’s thoughts about the society are written.